2010
DOI: 10.1590/s0074-02762010000100017
|View full text |Cite
|
Sign up to set email alerts
|

HBV markers in haemodialysis Brazilian patients: a prospective 12-month follow-up

Abstract: The aim of this study was to determine the prevalence and the incidence of hepatitis B virus (HBV) among haemodialysis (HD) subjects and to evaluate whether testing for serological markers at the time of admission is suitable for HBV screening in this population. One hundred twenty-three patients belonging to two HD centres from SãoPaulo, Brazil, were tested prospectively. HBV DNA was detected by polymerase chain reaction (PCR) and HBsAg was detected in 3.3% of patients. These authors were in agreement that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…The prevalence of both were higher than the prevalence found in the Southeast region (5.5% of HBsAg and 4% of anti-HBc) [ 19 ] and in a multicentre Brazilian study (1.4% of HBV prevalence) [ 26 ], but lower than the HBsAg prevalence in the South (10%) [ 27 ] and Central-West region (46.7%) [ 28 ]. These studies showed variable HBV prevalence rates in CRF population that may have been influenced by differences in organizational structure or the work process at haemodialysis centres, which includes the frequency of hygiene and sterilization of equipment in the dialysis room, reuse of capillaries and distribution of patients according to the number of health professionals [ 8 , 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of both were higher than the prevalence found in the Southeast region (5.5% of HBsAg and 4% of anti-HBc) [ 19 ] and in a multicentre Brazilian study (1.4% of HBV prevalence) [ 26 ], but lower than the HBsAg prevalence in the South (10%) [ 27 ] and Central-West region (46.7%) [ 28 ]. These studies showed variable HBV prevalence rates in CRF population that may have been influenced by differences in organizational structure or the work process at haemodialysis centres, which includes the frequency of hygiene and sterilization of equipment in the dialysis room, reuse of capillaries and distribution of patients according to the number of health professionals [ 8 , 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBV and HCV infections are prevalent worldwide, especially in the most vulnerable populations, such as patients infected with human immunodeficiency virus (HIV), patients with chronic renal failure (CRF) that are on haemodialysis and patients with coagulation disorders compared to the general population [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have documented a high prevalence of HBV infection in this study population. Other renal units have reported widely diverse rates of surface antigen positivity, for example, Turkey, Brazil, and USA and Europe of 13.3%, 18 2.4–10% 19 and 0.6–6%, 14 respectively. The Asia Pacific review of HBV and HCV infection in haemodialysis and peritoneal dialysis patients contained limited data regarding HBV with a wide range of prevalence estimates between 1.3% and 14% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, prevalence of HBsAg of 0, 2.4, 7, 10, 34.1% were reported in hemodialysis center in Southeast, Central, Northeast, South and Midwest regions of Brazil [78][79][80][81][82]. HBsAg prevalence of 4.5, 25, 1.4% was found in hemodialysis patients in Peru, Venezuela, Cuba [59,67].…”
Section: Hepatitis B and C Prevalence In Patients With Chronic Kidneymentioning
confidence: 99%